Clinicopathologic retrospective analysis of blastic plasmacytoid dendritic cell neoplasms - Owczarczyk-Saczonek, Agnieszka; Sokołowska-Wojdyło, Małgorzata; Olszewska, Berenika; Malek, Marta; Znajewska-Pander, Aleksandra; Kowalczyk, Anna; Biernat, Wojciech; Poniatowska-Broniek, Grażyna; Knopińska-Posłuszny, Wanda; Kozielec, Zygmunt; Nowicki, Roman; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is one of the aggressive rare hematopoietic malignancies with predilection to the skin, primarily found in adults. The precise incidence of BPDCN is difficult to estimate due to constantly changing nomenclature and lack of precise defining criteria prior to the 2008 WHO classification system. There are not many cases described in the literature, what makes the diagnostic process challenging. Skin lesions such as erythematous infiltrates and nodules are usually the first manifestation of the disease. Therefore, in doubtful diagnostic cases, dermatologists should perform histopathological and immunohistochemistry examinations along with hematological and oncological cooperation, as early diagnosis and appropriate treatment is essential for improvement of the disease course. This analysis, despite the small number of patients may provide useful information on the clinical and histopathological features of this rare malignancy.